Close Reduction Percutaneous Pinning (CRPP) versus Open Reduction Internal Fixation (ORIF) pada Fraktur Supracondylar Humerus Gartland Tipe II dan III pada Pasien Pediatri: Tinjauan Sistematis dan Meta-analisis - Astawa, Putu; Maharjana, Made Agus; Adisthanaya, Surya; Putra, Made Winatra Satya; Putra, Agus Suarjaya; Savio, Sherly Desnita (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Displaced supracondylar fracture in children is a challenging injury that may result in impaired functional and cosmetic outcome if not well-treated. Utilization of Closed Reduction and Percutaneus Pinning (CRPP) increased for this pathology, some authors believe ORIF results better anatomical reduction and lower rate of loss of reduction. Study aims to compare CRPP and ORIF for pediatric supracondylar humerus fracture. Method: Systematic review was conducted based on PRISMA guideline. Inclusion criteria were age less than 18 years old, comparing CRPP and ORIF for Supracondylar Humerus Fractures Gartland Type II, II.Studies of one surgical technique, Gartland type I, case reports were excluded. For meta-analysis, 6 studies were included and fixed effect model used to pool the result. In each study, mean difference (MD) with 95% confidence interval (CI) was calculated for dichotomous outcomes using Review Manager. Result: Total of 252 patients aged 0-15 years old were included. CRPP more often performed than ORIF. Satisfactory outcomes measured by Flynn’s criteria were achieved in 87.74% in CRPP and 86.73% in ORIF patient group, indicating significant difference (Heterogeneity, I2 = 23%; WMD, 1.26; 0.58 to 2.73; P =0.56). Conclusion: Current systematic review and meta-analysis suggest that for displaced supracondylar humerus fractures, ORIF offers a comparable functional and cosmetic outcome compared to CRPP.